2006
DOI: 10.1037/0735-7044.120.6.1279
|View full text |Cite
|
Sign up to set email alerts
|

Place learning strategy of substantia nigra pars compacta-lesioned rats.

Abstract: The substantia nigra pars compacta (SNc) and the dorsal striatum are often considered to be necessary for stimulus-response (S-R) habit learning, whereas the dorsal hippocampus is considered to be necessary for relational (declarative) memory. Spatial learning is a kind of relational learning that occurs when a rat is released from different locations (variable start) in a water maze to find a submerged platform that is kept in a constant location. However, when the rat is always released from the same startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
(56 reference statements)
5
14
0
1
Order By: Relevance
“…In rodents, dopamine depletion impairs spatial memory tasks (Da Cunha et al, 2006;Ferro et al, 2005;Miyoshi et al, 2002). Our study has confirmed that this is also true in motor learning.…”
Section: Cognitive Deficit Induced By Degeneration Of Nigrostriatal Psupporting
confidence: 91%
“…In rodents, dopamine depletion impairs spatial memory tasks (Da Cunha et al, 2006;Ferro et al, 2005;Miyoshi et al, 2002). Our study has confirmed that this is also true in motor learning.…”
Section: Cognitive Deficit Induced By Degeneration Of Nigrostriatal Psupporting
confidence: 91%
“…not able to learn this task (see also Figure 9C, left). Thus, the model is consistent with the experimental data showing that intact animals rely strongly on the locale strategy in this task and that lesions of the hippocampus (or NA) disrupt learning, whereas lesions along the taxon pathway (i.e., SNc or CP) do not produce any impairment (Da Cunha et al, 2006;Morris et al, 1982). Moreover, an analysis of the escape latency (see Figure 9A, left) revealed that when using locale strategy, the simulated rat learned rapidly during the first four to five trials and achieved, after approximately 15 trials, an asymptotic performance (Morris, 1981).…”
Section: Simulation 2: Hidden Goal Navigation In the Water Mazesupporting
confidence: 88%
“…Some models of PD are achieved by the use of neurotoxins, in particular 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), 6-hydroxydopamine (6-OHDA), and recently the endotoxin found in the outer membrane of gram-negative bacteria, lipopolysaccharide (LPS) [1][2][3]. In most of the studies of PD models, several of the motor, cognitive, affective, neurochemical, inflammatory and sleep disruptions encountered in the human disease are partially recapitulated by MPTP, 6-OHDA and LPS [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%